EFFICACY AND SAFETY OF CANNABINOIDS IN THE CONTROL OF CHRONIC PAIN IN PATIENTS WITH ADVANCED CANCER: AN INTEGRATIVE REVIEW - de Andrade, Brenda Dantas; Amin, Joice Rodrigues Rachid; de Barros, Larissa Luppi Monteiro; de Oliveira, Guilherme Nogueira Mendes (Seven Editora, 2025)
Introduction: This article aimed to perform an integrative review of clinical studies with patients with advanced cancer, evaluating the efficacy and safety of the use of cannabinoids as adjuvant therapy in the control of chronic pain. Methods: PubMed, Cochrane and Embase were searched, with the descriptors “Cannabinoids”, “Cannabidiol”, “Cannabis” and “Palliative Care”, to evaluate the efficacy and safety of the use of cannabinoids in the treatment of pain, with the main inclusion criterion being randomized clinical trials. Results: 181 articles were identified, screened by title, abstract and full reading (n=4), comparing mainly intervention, side effects and primary results. Discussion: Of the four clinical trials analyzed, two of them reached statistical significance (p=0.014), when comparing the pain reduction by the group using Nabiximols (THC/CBD) and placebo, while the other two presented p=0.0854 and p=0.84. The main side effects cited in the study were nausea and vomiting. Conclusion: Despite the divergence in statistical significance, all studies suggest that Nabiximols have clinical potential as an adjuvant therapy in pain reduction. DOI: https://doi.org/10.56238/sevened2025.028-003